Analysis of microalgae lipids isolated from basin of Kazakhstan, to assess the prospects of practical use (Experimental biology, 2015)
It was analyzed of fatty acid composition of 16 strains of microalgae lipid fractions isolated from different basins of Kazakhstan and characterized by stable active growth in the laboratory. Three species of green microalgae (Oocystis rhomboideus, Chlorococcum infusionum, Dictyochlorella globosa) and three species of diatoms (Synedra sp., Nitzshiasp., Pleurosigma attenuatum) are characterized by a high content of lipids and are promising for further study as a source of polyunsaturated fatty acids.
Keywords: green microalgae; diatoms; lipids; fatty acids; polyunsaturated fatty acids